The Relationship BetweenHIV Incidence Rate, District/ Municipality Health Budget, Healthy House Rate, and Tuberculosis Prevalence in Indonesia - Balgis -; Panji Fortuna H; Lukman Hifli (Masters Program in Public Health, 2016)
Background:Tuberculosis (TB) remains an important public health concern in the world including Indonesia. This study aimed to estimate the relationship between HIV incidence rate, district/ municipality health budget, healthy house rate, and tuberculosis prevalence in Indonesia. Subjects and Method:This was an analytic and observational study with ecologic study design. The data were obtained from 33 provinces, 497 districts/ municipalitiesthat were collected by Basic Health Research (Riset Kesehatan Dasar, Riskesdas)2013. The dependent variable was TB prevalence. The independent variables were HIV incidence rate, district/ municipality health budget, and healthy house rate. TB diagnosis was made by health personnel using sputum examination, chest X-ray photo, or both. The data were analyzed by multiple linear regression.Results:District/ municipality budget (b=-14.07;95% CI=-24.09to -4.05, p=0.080), and healthy house rate (b=-3.62; 95%CI=-6.28 to-0.96; p=0.009) decreased TB prevalence. HIV incidence rate (b=0.05,95% CI=0.02 to 0.08, p=0.002) increased TB prevalence. R2 was 56.5 % for this linear regression model, and the overall model was statistically significant (p=0.001).Conclusion:District/ municipality budget, healthy house rate, and HIV incidence rate are related with TB prevalence.Keywords:district/ municipality budget, healthy house rate, HIV incidence rate, TB prevalenceCorrespondence: Balgis. Department of Public Health, Faculty of Medicine, Sebelas Maret University, SurakartaJournal of Epidemiology and Public Health (2016), 1(3): 164-174https://doi.org/10.26911/jepublichealth.2016.01.03.03